2022
DOI: 10.2967/jnumed.122.264256
|View full text |Cite
|
Sign up to set email alerts
|

Early-Phase18F-Florbetapir and18F-Flutemetamol Images as Proxies of Brain Metabolism in a Memory Clinic Setting

Abstract: Alzheimer disease (AD) neuropathologic changes are b-amyloid (Ab) deposition, pathologic tau, and neurodegeneration. Dual-phase amyloid PET might be able to evaluate Ab deposition and neurodegeneration with a single tracer injection. Early-phase amyloid PET scans provide a proxy for cerebral perfusion, which has shown good correlations with neural dysfunction measured through metabolic consumption, whereas the late frames depict amyloid distribution. Our study aimed to assess the comparability between early-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For instance, a previous study observed different agreement between ePIB-PET and FDG-PET according to the amyloid status [24]. However, a recent study showed high agreement between ePET (using eFBP and eFMM tracers) and FDG-PET regardless of the amyloid positivity of the subjects [23]. Similarly, previous studies have shown an inverse relationship between amyloid deposition and CBF-ASL/FDG-PET [10].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, a previous study observed different agreement between ePIB-PET and FDG-PET according to the amyloid status [24]. However, a recent study showed high agreement between ePET (using eFBP and eFMM tracers) and FDG-PET regardless of the amyloid positivity of the subjects [23]. Similarly, previous studies have shown an inverse relationship between amyloid deposition and CBF-ASL/FDG-PET [10].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, we acknowledge differences between the current ePET protocol and the previously used ones. Namely, we used eFBP and eFMM tracers and analysed the static images, which have been recently shown to be capable to detect perfusion with a similar e cacy than FDG-PET [23]. On the other hand, early PIB-PET uptake shows slightly lower association than the ratio of tracer in ux extracted from dynamic PIB-PET in comparison to FDG-PET [24], as well different spatial patterns between both techniques [10,25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, amyloid PET is less invasive and better accepted by patients (indeed, in arm 3, 11% of participants explicitly wanted to undergo an amyloid PET, and 5% underwent amyloid PET because they refused lumbar puncture), and it is the biomarker of choice when lumbar puncture is contraindicated. Moreover, recent evidence shows that a dual-phase acquisition of amyloid PET imaging can also offer information on cortical perfusion (a proxy of metabolism and thus a measure of neurodegeneration) when additional early-phase images are acquired after tracer injection …”
Section: Discussionmentioning
confidence: 99%
“…9 This is mainly linked to the lack of studies showing, beyond its analytical and clinical validity, its impact on patients' management and care. With the first diseasemodifying therapies using amyloid-antibodies having been FDAapproved 55,56 , reimbursement status is gradually changing, as the proof of target expression may be required prior to initiation of an expensiveand not risk-freeantibody therapy. Currently, amyloid PET is reimbursed in Switzerland since August 2020, 84 in France since August 2022, 58 in the U.S since October 2023 59 and in Japan since November 2023.…”
Section: Amyloid Petmentioning
confidence: 99%